Evaluation of three commercial rapid kits to detect Cryptosporidium parvum in diarrhoeic calf stool. Issue 4 (2nd October 2018) - Papini, Roberto; Bonelli, Francesca; Montagnani, Marco; Sgorbini, Micaela
Abstract: The aim of this study was to evaluate three commercially available rapid immunochromatographic tests for detection of Cryptosporidium parvum antigens in faeces of naturally infected neonatal diarrhoeic calves. FASTest ® CRYPTO strip, FASTest ® CRYPTO-GIARDIA Strip and TETRASTRIPS ® were compared for their sensitivity, specificity, positive predictive value and negative predictive value using a cumulative positivity as gold standard. In addition, the agreement between each test and the gold standard was evaluated by Cohen's Kappa (k) value. The highest infection rate was observed by FASTest ® CRYPTO-GIARDIA Strip (65.15%), followed by FASTest ® CRYPTO strip (63.64%) and TETRASTRIPS ® (56.06%, ). A very good diagnostic performance of all the three tests was observed. FASTest ® CRYPTO strip ( k  = 0.935) and FASTest ® CRYPTO-GIARDIA Strip ( k  = 0.968) had the highest sensitivity (100%) while TETRASTRIPS ® ( k  = 0.875) had the highest specificity (100%). Eimeria spp oocysts were present in six samples but cross-reaction with this protozoan was not observed. These assays were not time-consuming and very easy to perform and to read. Based on our results, we recommend the use of FASTest ® CRYPTO strip, FASTest ® CRYPTO-GIARDIA Strip or/and TETRASTRIPS ® for detection of C. parvum antigens in faeces of neonatal diarrhoeic calves.